Colocolic Intussusception in an Adult Patient Secondary to Caecal Adenocarcinoma - Hicham Elmajdoubi; Marouane Baiss; Mohamed El Absi; El Hassan El Faricha El Alami; Mohamed El Ouanani; El Mahjoub Echarrab; Mohamed El Amraoui; Abdelkader Errougani (Case Reports in Gastrointestinal Medicine)
Acute intestinal invagination is the pathology of infants and small children. Its occurrence in adults is rare, and it represents 1 to 5% of intestinal occlusions often leading to the discovery of an organic cause that may be tumor. We report the case of a 72-year-old patient admitted to the emergency room of Ibn Sina Rabat, Morocco, for intestinal occlusion. The abdominal CT scan showed a voluminous intestinal invagination on a very probable heterogeneous digestive mass. The treatment was an open right hemicolectomy. The histopathological examination of the surgical specimen concluded a colonic well-differentiated adenocarcinoma with a 30% mucinous component. By review of literature, we discuss diagnostic and therapeutic procedures in emergency.